The haematopoietic stem cell niche: a new player in cardiovascular disease?. Issue 2 (24th December 2018) - Al-Sharea, Annas; Lee, Man Kit Sam; Purton, Louise E; Hawkins, Edwin D; Murphy, Andrew J
Abstract: Haematopoiesis, the process of blood production, can be altered during the initiation or progression of many diseases. Cardiovascular disease (CVD) has been shown to be heavily influenced by changes to the haematopoietic system, including the types and abundance of immune cells produced. It is now well established that innate immune cells are increased in people with CVD, and the mechanisms contributing to this can be vastly different depending on the risk factors or comorbidities present. Many of these changes begin at the level of the haematopoietic stem and progenitor cells (HSPCs) that reside in the bone marrow (BM). In general, the HSPCs and downstream myeloid progenitors are expanded via increased proliferation in the setting of atherosclerotic CVD. However, HSPCs can also be encouraged to leave the BM and colonise extramedullary sites (i.e. the spleen). Within the BM, HSPCs reside in specialized microenvironments, often referred to as a niche. To date in depth studies assessing the damage or dysregulation that occurs in the BM niche in varying CVDs are scarce. In this review, we provide a general overview of the complex components and interactions within the BM niche and how they influence the function of HSPCs. Additionally, we discuss the main findings regarding changes in the HSPC niche that influence the progression of CVD. We hypothesize that understanding the influence of the BM niche in CVD will aid in delineating new pathways for therapeutic interventions.